Effects of the application of IFRS 17 on the financial reporting of insurance companies – the Croatian case - Tominac, Sanja Broz (International Journal of Membrane Science and Technology, 2023)
International Financial Reporting Standard 4 is an interim standard published in 2004. Over the years, as the insurance industry has evolved, several fundamental issues have emerged suggesting that certain provisions of IFRS 4 are outdated or ineffective. Given the importance of the insurance industry, efforts have been made to correct these issues and publish a new standard that provides a simpler, more transparent and standardised determination of insurance contracts. In 2017, the IASB is publishing the new International Financial Reporting Standard 17 - Insurance Contracts, which aims to correct the inconsistencies caused by the application of IFRS 4, i.e. to ensure transparency, standardisation and comparability of the financial statements of insurance companies. The application of IFRS 17 aims to implement the equal treatment of insurance contracts between the companies themselves and within the group in order to carry out consolidation in a standardised manner. The aim is also to harmonise IFRS 17 with other standards, adjust estimates to reflect current market changes and also take into account financial effects and risks. The introduction of the new standard will have an impact on management, administration and employees, but also on external users of the financial statements, who will be able to monitor and compare the company's business in a clearer and more transparent way.